Perencanaan Strategis Sistem Informasi Pada Institusi Pendidikan Tinggi Menggunakan Analisis Critical Success Factors - Widyaningsih, Pipin; Mustafid, Mustafid; Rochim, Adian Fatchur (Universitas Diponegoro, 2011)
There are many organization which develop their information technology only based on the recommendation of certain vendors and colleagues. The development of Information and Technology Systems need a proper consideration in order to avoid the chance of bigger loss in the financial and investation sectors. The unsystematic development of Information and Technology Systems will not fu lfil a long term needs, there is no priority scale on it and it is not in line with the bu ssiness organization rhyme. The Strategic Planning Information System is a systematic approach about what is considered to be the most effective and effecient to fulfil the needs of information. The Strategic Planning Information System stated by Ward and Peppard (2002), which becomes the basis of this research, uses some analysis methods, likeValue Chain and Critical Success Factors. The result of this research is a blue print of the strategic planning which is based on the bussiness organization planning with the data gathered through the analysis method used and it involves all the organization component.Keywords: Strategic planning information system; Higher education institution, Critical success factors